The speed of dark - Moon, Elizabeth (Ballantine Books, 2004)
An exploration into the world of an autistic man who is offered a chance to try a brand-new experimental 'cure' for his condition. He must decide if he should submit to a surgery that might completely change the way he views the world, and the very essence of who he is.